Reduce inequality within and among countries - Chantal Line Carpentier; Richard Kozul-Wright; Fabio David Passos (UN Chronicle, 2015)
The Rio+20 negotiations began amidst the fallout from the 2008 financial crisis, which made it abundantly clear that the economic, social and environmental imbalances that had built up recently could no longer be tackled separately, sequentially, or by countries acting alone. Despite rapid export growth, strong capital inflows and high commodity prices in the developing world, the resulting income gains had been unevenly distributed, and many poorer countries and communities remained vulnerable to shocks and reversals. Crisis came in the wake of slow growth, massive income redistribution in favour of the top 1 per cent and an explosion in private debt, provoking not only a degree of moral soul-searching but also raising concerns about the fragility of the social compact.